THE IMPACT OF BIG FIVE PERSONALITY TRAITS ON WORK ENGAGEMENT AMONG MALAYSIAN PUBLIC UNIVERSITIES ACADEMICS - Siti Balkis Mohamed Ibrahim; Nur Qurratul’ Aini Ismail; Nazra Aliff Nazri; Nurhidayah Marzuki@Yahaya; Faiz Masnan; Nur Hafifa Iswati Ishak; Rohaiza Mohamad Idaris, (Journal of Human Development and Communication (JoHDeC), 2025)
This study focuses on the public universities’ academics work engagement levels based on the individual personality traits that influences them. It is believed that individual personality has a credentials to a person’s attitude or features, which most of the time, being influenced by internal and external factors. Thus, in this study context, researchers’ intented to test academics’ personality while their engaging with their tasks. This study executed in Malaysia context, survey tested on 147 participants or said 147 academics. The participation indicates 64% of responses. Later, the responses of questionnaires were coded thru SPSS version 26. There are six analyses were executed in this study, namely descriptive analysis, normality analysis, reliability tests, Pearson correlation analysis, simple regression analysis and also multiple regression analysis. Results shows that Big Five personality model are interrelated and correlated with work engagement which aligned with previous studies, except for agreeableness personality that been contradicted with past research in this study context. There is high possibility due to various situational issues, such as in aspect of sampling method or misinterpretation by respondents. Moreover, this study tends to be a contribution to literature and stepping stone for more outcomes. Future studies were proposed.